The effect of induced sadness and moderate depression on attention networks. Issue 6 (18th August 2017) - Bellaera, Lauren; von Mühlenen, Adrian
ABSTRACT: This study investigates how sadness and minor/moderate depression influences the three functions of attention: alerting, orienting, and executive control using the Attention Network Test. The aim of the study is to investigate whether minor-to-moderate depression is more similar to sadness or clinical depression with regard to attentional processing. It was predicted that both induced sadness and minor-to-moderate depression will influence executive control by narrowing spatial attention and in turn this will lead to less interference from the flanker items (i.e. less effects of congruency) due to a focused attentional state. No differences were predicted for alerting or orienting functions. The results from the two experiments, the first inducing sadness (Experiment 1) and the second measuring subclinical depression (Experiment 2), show that, as expected, participants who are sad or minor to moderately depressed showed less flanker interference compared to participants who were neither sad nor depressed. This study provides strong evidence, that irrespective of its aetiology, sadness and minor/moderate depression have similar effects on spatial attention.